2008
DOI: 10.1556/aling.55.2008.3-4.9
|View full text |Cite
|
Sign up to set email alerts
|

Contrastive focus and emphasis

Abstract: The paper puts forward a discourse-semantic account of the notoriously evasive phenomena of contrastivity and emphasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 14 publications
4
41
0
4
Order By: Relevance
“…It was found that these realizations do not differ in their semantic type (Green & Jaggar 2003, Hartmann & Zimmermann 2007: instead, the marked form signals that the focused constituent (or the whole speech act) is unexpected for the hearer (Zimmermann 2008). These assumptions are consistent with findings for other African languages (Fiedler et al 2006).…”
Section: Using Annis An Example Querysupporting
confidence: 70%
“…It was found that these realizations do not differ in their semantic type (Green & Jaggar 2003, Hartmann & Zimmermann 2007: instead, the marked form signals that the focused constituent (or the whole speech act) is unexpected for the hearer (Zimmermann 2008). These assumptions are consistent with findings for other African languages (Fiedler et al 2006).…”
Section: Using Annis An Example Querysupporting
confidence: 70%
“…41 It is for this reason that structures like (43B) have been dubbed "partial focus movement" (Zimmermann 2007; see also Fanselow & Lenertová 2010). To put it differently, the answer (43B) apparently shows the coexistence of two overlapping foci: the broad focus required by question-answer congruence, and the narrow focus on the direct object which supports the mirative implicature.…”
Section: :36mentioning
confidence: 99%
“…We have characterized the mirative import as a conventional implicature but, following an insight of Zimmermann (2007), we have argued that it is not purely anchored to the speaker: it is based on a shared modal base (the context set) and on an ordering source that can be anchored to one of the conversational participants, or to the whole conversational community.…”
Section: Concluding Remarks and Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…This kind of fronting has been taken to convey the implicature that the proffered information is unexpected or suprising (Abeillé et al 2008, Zimmermann 2007 accordingly, I will label this type of import 'mirative import'.…”
Section: The Mirative Importmentioning
confidence: 99%